FRONT OFFICEâ€™S â€œICE BREAKERâ€ WITHIN THE HOSPITALITY INDUSTRY: A TRANSLATION STUDY - Habibah Aini Noor; Ni Made Diana Erfiani (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2023)
In the context of the hospitality sector, effective communication at the front desk plays apivotal role in guest satisfaction and overall service quality. This study aims to identify thesubtleties of the linguistic and cultural obstacles encountered at the front desk during thecritical "ice-breaker" conversation period. Applying Newmarkâ€™s translation methods, this studyexamines how linguistic nuances, cultural subtleties, and pragmatic considerations influencethe translation of ice-breaking phrases commonly used in the hospitality sector. Throughqualitative analysis and case studies, it seeks to unravel the complexities of translation in thecontext of front-desk interactions, shedding light on the challenges faced and strategiesemployed. The results of this study provide valuable insights into the translation process andvaluable perspectives for refining translation strategies in the hospitality industry.